Muscular dystrophy associated with the DMD gene in women - E. O. Vorontsova; A. V. Zinina; O. A. Shchagina (Нервно-мышечные болезни, 2024)
Dystrophinopathies are a spectrum of X-linked muscular disorders associated with pathogenic/likely pathogenic variants in the dystrophin gene (DMD). Typically, the condition develops in males, but cases of symptom manifestation have also been described in females. The review presents contemporary data on the manifestations of dystrophinopathies in women with pathogenic variants in the DMD gene, discussing the reasons for the varying degrees of symptom expression in carrier women with pathogenic/ likely pathogenic variants. It discusses the importance of mutation screening in the DMD gene for women presenting with muscular dystrophy symptoms and investigating carrier status in relatives of patients with Duchenne/Becker muscular dystrophy.